Bank-specific and macroeconomic determinants of bank performance: A comparative analysis between islamic and conventional banks in Malaysia - Ali, Faida Abdalla (2017)
The aim of this study is to examine the determinants of conventional and Islamic bank performance in Malaysia. A panel data sample of 23 conventional banks and 16 Islamic banks for the period 2008 to 2015 was used. The independent variables were categorised into bank-specific factors and macroeconomic factors. The bank-specific factors were capital adequacy, operating efficiency, asset quality, bank-size, and liquidity whereby GDP and inflation used as macroeconomic variables. The Generalized Least Square (GLS) was used for testing the hypotheses of the study. The regression results show that asset quality, operational efficiency, liquidity, bank size, GDP and inflation are significant determinants of conventional bank performance, while, capital adequacy, asset quality, operational efficiency, bank size, and GDP are significant with Islamic bank performance. It is worth to mention that asset quality is the only factor that bring the same effect to the performance of conventional and Islamic banks, which is found to be positive and statistically significant using either ROA or ROE. This study concludes that there are differences in the direction of the effects of the selected variables on the conventional and Islamic bank performance. Also, the study concludes that factors that affect conventional bank performance are not necessarily to affect Islamic bank performance